Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1998
DOI: 10.1115/98-gt-384
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Emission Abatement in IGCC Power Plants by Semiclosed Cycles: Part A — With Oxygen-Blown Combustion

Abstract: This paper analyzes the fundamentals of IGCC power plants where carbon dioxide produced by syngas combustion can be removed, liquefied and eventually disposed, to limit the environmental problems due to the "greenhouse effect". To achieve this goal, a semiclosed-loop gas turbine cycle using an highlyenriched CO 2 mixture as working fluid was adopted. As the oxidizer, syngas combustion utilizes oxygen produced by an air separation unit. Combustion gases mainly consist of CO 2 and 1420: after expansion, heat rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…ψ= volume flow of recirculated CO volume flow of the compressor inlet flow 2 (5) Prediction of compressor performance at identical Π N Th e Π N here is set to a level at which the compressor operates with air as a working fl uid. Th e normalized pressure ratio and isentropic effi ciency predicted using the throughfl ow analysis are illustrated in Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ψ= volume flow of recirculated CO volume flow of the compressor inlet flow 2 (5) Prediction of compressor performance at identical Π N Th e Π N here is set to a level at which the compressor operates with air as a working fl uid. Th e normalized pressure ratio and isentropic effi ciency predicted using the throughfl ow analysis are illustrated in Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Some extra devices, such as air separation and CO 2 liquefaction units, have been proposed to be added to the traditional power plant. 5 Modifi cations are also required to adapt gas turbines to the new working fl uid and oxy-fuel combustion. 6 Th us, continuous eff orts have been made to predict the working characteristics of various components in the cycle and to handle such a new power plant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the more common proposal is being applied through gasification of coal to produce syngas which should be purified before using it the power cycle. In their research, Chiesa and Consonni [145] and Chiesa and Lozza [146,147] compared three different technologies of integrating carbon capturing with coal syngas. The first approach is to integrate water-gas shift with syngas for hydrogen production, and CO 2 separation the before combustion.…”
Section: Application Of Coal Oxycombustion In Power Cyclesmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] When comparing capture options, appropriate importance must be given to the efficiency, reliability, and cost of not-currently available technologies. For example, some of the capture technologies presented in the existing literature such as semiclosed cycles 12,16 and the Matiant cycle 14 use CO 2 as a working fluid in the gas turbine and will require development of modified gas turbines. Several IGCC studies 17,19,20 have also shown that improved system integration can increase overall plant efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of researchers has used steady-state simulation and analysis tools to evaluate IGCC plant performance and efficiency, including the impact of different CO 2 capture technologies. When comparing capture options, appropriate importance must be given to the efficiency, reliability, and cost of not-currently available technologies. For example, some of the capture technologies presented in the existing literature such as semiclosed cycles , and the Matiant cycle use CO 2 as a working fluid in the gas turbine and will require development of modified gas turbines. Several IGCC studies ,, have also shown that improved system integration can increase overall plant efficiency.…”
Section: Introductionmentioning
confidence: 99%